Storyline for health promoting in persons with hypertension - ส่งวัฒนายุทธ, ปาณิสรา; ศิริกุลวิวัฒน์, จินต์ทิพา (Journal of The Royal Thai Army Nurses, 2019)
The health promotion is crucial for prevention and control blood pressure in person with hypertension for decreasing dangerous life complication. The important health promotion role of nurse has health education demonstration and training skills for changing health behavior. The storytelling in group of hypertensive patients helps member for exchanging experience, increasing motivation, understanding change behaviors. Moreover, it help the problem solving, help together lead to conduct new knowledge and can implicate, build confidence, and change lifestyle in order to control blood pressure and good quality of life.